Conceptualization of health and diseas in Qur`anic context and its implications on modern medical practices - Shogar, Ibrahim (2016)
Background: Health, disease and sickness are complex medical concepts that indispensably related to human life. The analytical study of such concepts is essential for medical philosophy which aims at perfection of healthcare methods. The critical question on such attempt however emanates from the fact that these concepts are elusive. The World Health Organization (WHO) has defined Health as “a state of complete physical, social and mental well-being, and not merely the absence of disease or infirmity”; but this attempt, in fact, describes what ‘should be’ rather than ‘what is’. The two major questions raised by above fact are about (i) the sickness / disease as described by the physician and as experienced by the patient (ii) what is the proper method of treatment if the two concepts (of doctor & patient) are not identical.